ASSOCIATION BETWEEN ANTIHYPERTENSIVE TREATMENT IN PREECLAMPSIA PATIENTS WITH INCIDENCE OF BIRTH ASPHYXIA AND LOW BIRTH WEIGHT IN RSUP DR. HASAN SADIKIN BANDUNG - Fatmawati Sitorus, Mutia
Preeclampsia is one of the three major causes of maternal death in Indonesia. In addition to causes maternal mortality and morbidity, infants born to people with preeclampsia are at risk of being born with a low birth weight / LBW (<2500 g) and asphyxia. In Indonesia, data regarding the use of certain antihypertensive as the first line in treatment of hypertension in pregnancy and their impact on perinatal is not sufficient. This study aims to explore the association and effects of antihypertensive therapy in patients with preeclampsia on infants outcome (LBW & asphyxia). The study was conducted on 182 patients with preeclampsia who were treated at RSUP Dr. Hasan Sadikin Bandung during 2018. Comparative analysis was performed between antihypertensive groups with the One-way ANOVA and Kruskal-Wallis tests. The result of the analysis showed that there were statistically significant differences in infant body weight (p<0.05; CI95%) between preeclampsia patients receiving antihypertension therapy (2227 g ± 779.8) and those not receiving antihypertension therapy (2696 g ± 667.2). There were no significant differences in APGAR scores between the groups treated with antihypertensive (p>0.05; CI95%). There were no statistically significant differences (p>0.05; CI95%) between several groups of antihypertensive therapy giving a tendency towards both incidences. The methyldopa combination therapy group with other antihypertensives (amlodipine, nicardipine, furosemide, and spironolactone) had the highest proportion in giving a tendency towards LBW incidence (75.0%) and neonatal asphyxia (17.9%).